Wide view of Cloverdale Avenue and Miller Street. - Jones, Frank (Forsyth County Public Library, 2008)
Photo made in the 1960s.
Wide view of Cloverdale Avenue and Miller Street. Cloverdale Avenue runs left to right in the photo. The photo was taken before either side of the Cloverdale hill near Interstate 40 was developed.
Keywords: Forsyth County (N.C.) -- History -- Sources; Forsyth County (N.C.) -- History -- Pictorial works; Digital Forsyth